靈樞·腸胃에 대한 연구 - 정헌영(Heon Young Jeong) (동의생리병리학회지, 2006)
Jangwi(腸胃) was recorded to Young Chu(靈樞)'s volume 33. Also, This Was recorded in Tae So(太素)'s volume 10 Sindo Jangdo(身度 腸道), Gap Eul(甲乙)'s volume 2 Goldojangdojangwisosujechil(骨度腸道腸胃所受第七) and You Gyung(類經)'s volume 4 Jangsnagyou Jangwidaesojisu(臟象類 腸胃大小之數). Reason which call that it is Jangwi(腸胃) is that is describing length, width, diameter, weight, capacity, bends state of digestive organ from mouth to rectum. This chapter can not be understood in view of yin and yang five elements with Makedo(맥도), Goldo(骨度). This chapter can approach from specially viewpoint that is anatomy. Name of This chapter's terminology and position and types are very realistic. I feel pity that study does not exist about this. Therefore, I compared with comments of several doctors and modern anatomy. I believe that will be beaconed to understand This chapter. KCI Citation Count: 0